2017
DOI: 10.1055/s-0037-1604396
|View full text |Cite
|
Sign up to set email alerts
|

Botox and Thumb MCP Radial Collateral Ligament Reconstruction

Abstract: We report the use of botulinum toxin to aid in the treatment of chronic radial collateral ligament insufficiency of the thumb. Treatment included autograft tendon reconstruction and cast immobilization. Six weeks postoperatively, prior to hand therapy, the patient underwent an ultrasound-guided botulinum neurotoxin A injection into the adductor pollicis muscle to negate its deforming forces on the reconstruction. The patient made an excellent recovery and 1 year postoperatively was pain free and had a stable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Bioprotection with botulinum toxin via intramuscular injection was shown to be effective first in an Achilles tendon model in the rat, such that the muscle was incapable of actively producing enough force to rupture the repaired Achilles tendon. 13 Multiple clinical studies have followed with successful use in zone 2 finger flexor tendon repairs, 12 distal biceps tendon repair, 19 thumb MCP radial collateral ligament reconstruction, 20 with the benefits of decreased stress placed on the repair, and decreasing pain associated with the repair.…”
Section: Discussionmentioning
confidence: 99%
“…Bioprotection with botulinum toxin via intramuscular injection was shown to be effective first in an Achilles tendon model in the rat, such that the muscle was incapable of actively producing enough force to rupture the repaired Achilles tendon. 13 Multiple clinical studies have followed with successful use in zone 2 finger flexor tendon repairs, 12 distal biceps tendon repair, 19 thumb MCP radial collateral ligament reconstruction, 20 with the benefits of decreased stress placed on the repair, and decreasing pain associated with the repair.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, graft contraction and continuation of palmar subluxation may also cause joint stiffness. Cates et al [16] reconstructed chronic RCL rupture with free PL autograft and biotenodesis screw, injected botulinum toxin to adductor pollicis muscle before starting physical therapy to protect RCL reconstruction from deforming force of adductor pollicis and start earlier motion, and reported that botulinum toxin may decrease the period of immobilization.…”
Section: Discussionmentioning
confidence: 99%